Menganalisis Zakat sebagai Sarana Ketahanan dan Pemulihan Ekonomi melalui Kerangka Kerja Berbasis Syariah untuk Memperkuat Stabilitas Keuangan Pasca-Krisis - Naveed Khan; Ghulam Muhammad (Muttaqien, 2026)
This study explores the role of Zakat as a strategic Islamic financial instrument in fostering socio-economic strengthening, supporting sustainable recovery, and promoting equitable wealth redistribution in the post-crisis era. Employing a qualitative analytical approach that integrates classical Islamic sources, contemporary research, and comparative evaluations, the study demonstrates that Zakat transcends the function of mere ritual worship. Zakat operates as a structured socio-economic system capable of proactively protecting vulnerable groups from economic shocks and social fragility. The findings indicate that integrating Zakat into national development strategies through transparent institutional governance can bolster financial stability, enhance workforce participation, and break the cycle of aid dependency by providing a dignified pathway out of poverty. While acknowledging limitations regarding empirical data availability and administrative variations across Muslim nations, the study offers practical implications by providing a robust Shari'ah-based framework for policymakers to optimize welfare governance. The originality of this research lies in its demonstration of the ethical, equitable, and sustainable dimensions of Zakat, qualities that distinguish it from conventional welfare models, while affirming its capacity as a cornerstone for building an inclusive, resilient socio-economic order capable of withstanding crises.